Old age’s muzzled sorrows in Lygia Fagundes Telles and Clarice Lispector - Rabelo Câmara, Yls (2019)
This article aims to show the concept of old age in Brazil of the seventies through the analysis of “Senhor Diretor” and “A partida do trem”, two short stories written by Lygia Fagundes Telles (1977) and Clarice Lispector (1974), respectively. To do so, we did a bibliographical survey and, based on theorists such as Ferreira (2014) and Beauvoir (1990), among others, we analyzed psychologically and literarily the characters Maria Emília and Maria Rita, the protagonists of the short stories mentioned above. By placing them alongside each other, we see how aging can be marked by negative modes of subjectivation that cause suffering due to rejection, low self-esteem, loneliness, the introjection of preconceived notions, denial of sexuality, and hopelessness. And while the short stories reinforce these socio-historically constructed standards, this research is also relevant in showing old age under a prism of fullness and a search for meaning in life.